(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This essay is about some prospects opened up by neurosciences for the current civil law. Just think about the discovery of the mirror-neurons and the possible use of it in the negotiation (it imposes the protection of self-determination and consensus of the contracting party); or about the consequences deriving from neuro-scientific knowledge for the notion of legal capacity (or actual abilities) of natural persons. This provides a good guess of how valuable the neuro-scientific knowledge could be for the more effective and efficient protection of the human dignity.